Perceived constraints to investments in the JSE Alt-X by professional portfolio managers - Niemann, Martin Phillip (My University, 2012)
The study set out to understand the factors constraining investment in companies listed on the JSE Alt-X exchange by professional portfolio managers. This was especially relevant within the context of continued focus by the literature on the limited success of the JSE Alt-X in attracting investments from professional portfolio managers (Claasen 2009; Rego 2009; Minney 2010; Greenhill 2010). These articles expressed concerns around the continued viability of the stock exchange, and the impact the lack of investor interest would have on listed companies’ future growth plans. Identifying constraints to investment for professional portfolio managers would assist in providing guidance to the Alt-X board in understanding the obstacles facing the exchange in attracting investments, as well as assisting portfolio managers in better understanding the factors that limit their ability to provide a greater range of potential investment options to their clients. Data was gathered through semi-structured interviews, allowing an opportunity to explore perceptions and reasons behind the answers provided by the respondents, as well as allowing respondents the ability to raise concerns and additional constraints that might not have been highlighted by the literature review. The study found liquidity, availability and perceived integrity of information, as well as reputation to be the greatest constraints to investment in the JSE Alt-X. Corporate governance was perceived as having the lowest constraining impact, with the majority of correspondents indicating that they were satisfied with this aspect of the exchange. Recent performance was also not perceived as a significant constraint, due to the limited importance placed on this factor in the investment decision making process. The JSE Alt-X provides an important platform for the growth and maturation of companies and management within South Africa and it is therefore imperative for the exchange to remain a sustainable and attractive investment option to support the growth of these companies. Addressing these constraints will assist in attracting greater investment to the exchange, providing greater capital support to fund job creation, growth and wealth creation within South Africa.
MBA thesis - WBS
Keywords: Alt-X exchange; Johannesburg Securities Exchange; Portfolio managers